Media Sosial dan Budaya Politik Generasi Milineal dalam Pemilu - Kokom Komariah; Dede Sri Kartini (ARISTO, 2019)
Social media nowadays has been crutial part of human being life particularly for the genarations those are so called millenial. The massive use of social media is not merely functioned for the social purpose such as information sharing among them but also has been used for business and economic or even political purposes. The local election of the Jawa Barat province in the year of 2018 is a moment where the millineal generation functioned the social media such as facebook and whattsap for the political purposes. This article discusses the phenomenon of using internet-based social media as an instrument in political communication and campaigning in the local election of West Java Province in 2018 as well as discussing the effectiveness of the media contents in shaping the pattern of millennial generation political behavior. The research adopts is qualitative approach by taking the object of research on political communication, as well as culture and political behavior. The main informants from this study were beginner voters who also catogerisaed as the group of the millennial generation. This study found that social media contents in general became an important instrument in shaping the pattern of political behavior of the millennial generation. The roles of the media for instance are indicated that current life of the millennial generation that cannot be separated from such media, social media contents provides political knowledges about profiles of candidates in local election, social media content provided political education both related to the technical implementation of the election and also the vision and mission of the candidates and, millennial generation have their respective communities which they make as a forum for discussion about the social media contents.